Engineered herpes simplex virus DNA polymerase point mutants: the most highly conserved region shared among alpha-like DNA polymerases is involved in substrate recognition. - Marcy, A I (1990)
Eucaryotic, viral, and bacteriophage DNA polymerases of the alpha-like family share blocks of sequence similarity, the most conserved of which has been designated region I. Region I includes a YGDTDS motif that is almost invariant within the alpha-like family and that is similar to a motif conserved among RNA-directed polymerases and also includes adjacent amino acids that are more moderately conserved. To study the function of these conserved amino acids in vivo, site-specific mutagenesis was used to generate herpes simplex virus region I mutants. A recombinant virus constructed to contain a mutation within the nearly invariant YGDTDS motif was severely impaired for growth on Vero cells which do not contain a viral polymerase gene. However, three recombinants constructed to contain mutations altering more moderately conserved residues grew on Vero cells and exhibited altered sensitivities to nucleoside and PPi analogs and to aphidicolin. Marker rescue and DNA sequencing of one such recombinant demonstrated that the region I alteration confers the altered drug sensitivity phenotype. These results indicate that this region has an essential role in polymerase function in vivo and is involved directly or indirectly in drug and substrate recognition.